Novel Angular and Polarization Independent Band-Stop Frequency Selective Surface for Ultra-Wide Band Applications - A. Kocakaya; S. Çimen; G. Çakır (Radioengineering, 2019)
A novel compact band-stop frequency selective surface (FSS) with angular and polarization stability performance for ultra-wide band (UWB) applications is presented in this paper. The presented FSS consists of square loop element and a crossed dipole with ring aperture element. The novel unit cell size is miniaturized to 0.047λ × 0.047λ, where λ is free-space wavelength corresponding to the lowest frequency of the UWB band. The -3dB bandwidth of the proposed FSS is between 3.05 GHz and 10.73 GHz frequencies which are cover the whole UWB band that is defined by FCC. Due to compact size of unit cell, the presented FSS has good angular stability up to 60° incident angles both perpendicular (TE) and parallel (TM) polarization. The resonance frequency deviation is maximum 1.75% for TE polarization. In addition, proposed FSS has excellent stable resonant frequency. The designed FSS is fabricated and experimental measurements are done. There is consistency between numerical simulations with measurement results.